DIFFERENTIAL DIAGNOSIS OF MITOCHONDRIAL NEUROGASTROINTESTINAL ENCEPHALOMYOPATHY. FIRST CLINICAL DESCRIPTION IN RUSSIA - Kurbatov, S. A.; Fedotov, V. P.; Tsygankova, P. G.; Zakharova, E. Y.; Lipovka, S. N. (Nervno-myshechnye bolezni, 2015)
Mitochondrial neurogastrointestinal encephalomyopathy syndrome (MNGIE) is a rare autosomal recessive progressive multisystem disorder. Most of MNGIE is caused by mutations in the gene encoding thymidine phosphorylase (TYMP), locus 22q13. Mitochondrial dysfunction represents multiple deletions and depletion of mtDNA. We present a case of MNGIE with a novel mutation in the position c.1001T>G of TYMP gene, hypergonadotropic hypogonadism, decrement of compound muscle action potential following repetitive nerve stimulation on EMG which was not previously described in literature and differential diagnoses MNGIE with other conditions.